Room temperature ferromagnetism promoted by defects at zinc sites in Mn-doped ZnO - Almeida, V. M. de; Mesquita, A. [UNESP]; Zevallos, A. O. de; Mamani, N. C.; Neves, P. P.; Gratens, X.; Chitta, V. A.; Ferraz, W. B.; Doriguetto, A. C.; Sabioni, A. C. S.; Carvalho, H. B. de (Elsevier B.V., 2016)
The nature of the room temperature ferromagnetism in dilute magnetic oxides is still a matter of debate. However, there is a consensus that structural point defects play an important role to achieve a desired long range ferromagnetic order. In this report we have clearly established a correlation between an observed room temperature ferromagnetism and defects at zinc sites for Mn-doped ZnO (Zn0.93Mn0.03O) samples prepared by the solid state reaction method and subject to post-annealing under reducing atmosphere. Detailed microstructural analysis was carried out to exclude the presence of extrinsic sources of ferromagnetism. Photoluminescence and Hall measurements reveal that the main present defects in the samples are associated to defects at the zinc sites. Magnetic characterization demonstrates a room temperature ferromagnetic behavior associated to a paramagnetic Curie-Weiss component. The magnetization and density of defects expressively reduces after the post-annealing. In this context, the defect mediated magnetic coupling between Mn atoms under the scope of the bound magnetic polaron model and the d(0) ferromagnetism are used to interpret the magnetic properties. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Dilute magnetic oxides; Mn-doped ZnO; Defect related magnetism; Structural and magnetic characterization